Fever is associated with higher morbidity and clot burden in patients with acute pulmonary embolism. Issue 1 (23rd September 2018) - Saad, Muhammad; Shaikh, Danial H; Mantri, Nikhitha; Alemam, Ahmed; Zhang, Aiyi; Adrish, Muhammad
Abstract : Background: Fever is considered as a presenting symptom of pulmonary embolism (PE). We aim to evaluate the association between PE and fever, its clinical characteristics, outcomes and role in prognosis. Methods: A retrospective chart review of patients who were hospitalised with the diagnosis of acute PE was conducted. Patients in whom underlying fever could also be attributable to an underlying infection were also excluded. Results: A total of 241 patients met the study criteria. 63 patients (25.7%) had fever within 1 week of diagnosis of PE of which four patients had fever that could be due to underlying infection and were excluded. Patients in PE with fever group were younger compared with PE without fever group (52.52 vs 58.68, p=0.012) and had higher incidence of smoking (44.1% vs 20.9%, p<0.001). Patients in PE with fever group were more likely to require intensive care admission (69.5% vs 35.7%, p<0.001), had a longer hospital length of stay (19.80 vs 12.20, p<0.001) and higher requirement of mechanical ventilation (30.5% vs 6.6%, p<0.001) compared with those without fever. PE with fever group were more likely to have massive and submassive PE (55.9% vs 36.8%, p=0.015) and had higher incidence of deep vein thrombosis (33.3% vs 17.4%, p=0.0347) compared with PE without fever. In a univariate model, there was higher likelihood of in-hospital mortality in PE with fever group compared with PE without fever (22.0% vs 10.4%, p=0.039). Conclusion: Patients with acute PE and fever have higher morbidity and clot burden.